THE RELATIONSHIP BETWEEN SUBMANDIBULAR ABSCESS AND ODONTOGENIC INFECTION AT SITI KHADIJAH HOSPITAL DURING THE PERIOD JANUARY 2016 – NOVEMBER 2021 - Andi Fikri Agussalim; Yohni Wahyu Finansah; Yuli Wahyu Rahmawati; Brilliant Citra Wirashada; Nurma Yuliyanasari (Sean Institute, 2023)
Submandibular abscess is an inflammation and is accompanied by pus formation in the submandibular region and there are clinical symptoms in the form of sore throat, fever and limited movement of opening the mouth. Submandibular abscess is included in one of the odontogenic abscesses that are often found, cases increase in the transition season when the human body's immunity decreases causing the body to be less able to fight bacteria, this abscess comes from premolars or molars a lower jaw that spreads in a lingual direction below m. Mylohyoid. Knowing the relationship between submandibular abscesses and odontogenic infections. This type of study is observational using the cross sectional method in hospitals. Siti Khadija Throughout. Samples are selected by consecutive sampling. Data collection of submandibular abscesses and odontogenic infections were taken from medical records. The results of the medical record were analyzed with the Spearman correlation analysis test. Theistic characteristics of submandibular abscess patients at Siti Khodijah Muhammadiyah Hospital Branch Along Sidoarjo that were observed in this study were gender, age, occupation, length of treatment, comorbidities, complications and management. There was no significant association between age with submandibular abscesses and sex with submandibular abscesses (p > 0.05). The largest types of odontogenic infections in the study were cellulitis and mouth abscesses (86.5%). There was a significant association between submandibular abscess and odontogenic infection with the contingency correlation test (p<0.05) and with the Spearman correlation test (p<0.05). There is a significant association between submandibular abscesses and odontogenic infections.